Lactato sérico como método diagnóstico, pronostico y de seguimiento terapéutico en pacientes críticos del Hospital General Teófilo Dávila - Briones Tinoco, Ginger Mishel (2020)
In recent years, the presence of hypoperfusion has been demonstrated even in the absence of hypotension and / or clinical signs, being considered a factor associated with significantly elevated morbidity and mortality, as well as the documentation of hyperlactatemia is associated with the existence of "debt of oxygen "in tissues, relating for this reason to an increase in mortality. For this reason, this work aims to contribute to knowledge, highlighting and emphasizing the importance of diagnostic value, prognosis and therapeutic follow-up depending on the severity of admission to the ICU, and the existing relationship between serum lactate levels and the severity of tissue hypoperfusion. The present study is observational-descriptive-correlational, cross-sectional, with a quantitative approach, with a total population of 95 patients admitted to the Intensive Care Unit of the General Teófilo Dávila Hospital in the city of Machala, for which the levels were reviewed. of lactate and determined in the laboratory of the same and state of hipoperfusión, said data were analyzed in the statistical program SPSS. The results obtained showed that the average age range was 20-64 years, with the majority of cases being women with 36.8%. 66.3% presented serum lactate values between 0.6-1.2mmol / L; 23.2% presented values between 1.3-3.9mmol / L and 10.5% presented values> 4mmol / L, of the total of cases in relation to the hospital stay, 71.5% was 0-5 days, followed by 6-10 days with 22.1%. Among the most frequent pathologies were: neurologics, cardiovascular and endocrinometabolics. Key Words: Hyperperfusion, Lactate, trauma, hypovolemic shock, sepsis